The influence of a destination’s red cultural atmospherics on tourists’ confidence in Chinese culture - Zhou, Xiaoli; Guo, Yulin; Xie, Xiaofeng; Liu, Chunjuan; Zhang, Fengying (Frontiers in Psychology, 2022)
This study explores the development of tourists’ confidence in Chinese culture through red tourism. Partial least squares structural equation modeling (PLS-SEM) was adopted to analyze the survey data collected from red tourists in Wuxiang county, Changzhi, Shanxi province, China to examine the influence of a destination’s red cultural atmospherics on tourists’ confidence in Chinese culture. The results indicated that Wuxiang’s red cultural atmospherics composed of physical atmospherics, spiritual atmospherics and institutional atmospherics significantly influences tourists’ confidence in Chinese culture. Tourists’ perception of red education and their red cultural identity mediate the impact of the destination’s red cultural atmospherics on tourists’ confidence in Chinese culture. These findings contribute to the red tourism literature by providing empirical support for building tourists’ confidence in Chinese culture through red tourism. The empirical results also offer managerial implications for red tourism destinations’ planning and management.